PENGARUH PENGGUNAAN METODE PEMBELAJARAN BERBASIS PERMAINAN TRADISIONAL (DENDE-DENDE) TERHADAP PEMAHAMAN KONSEP TATA BAHASA BAHASA INDONESIA SISWA KELAS II SD MUHAMMADIYAH 3 MAKASSAR - Mutiara Nur; Muhammad Akhir; Anzar (STKIP Subang, 2025)
The research used in this study was experimental research. Experimental research is one type of quantitative research that aims to determine whether there is an effect of using traditional game-based learning methods (dende-dende) on understanding the concept of Indonesian grammar for grade II students of Muhammadiyah 3 Makassar Elementary School. The subjects of this study were grade II students of SD Muhammadiyah 3 Makassar. In the even semester of the 2025/2026 school year totaling 20 people divided into two classes, namely classes II A and II B. The research was conducted for 6 meetings which were divided into 3 meetings in the experimental class and 3 meetings in the control class. Data collection techniques were carried out using learning outcome tests, namely posttest and pretest and observation data. The collected data were analyzed using quantitative analysis and qualitative analysis. Based on the results of the study that there is an effect of the use of traditional game-based learning methods (dende-dende) on understanding the concept of Indonesian grammar of grade II students of SD Muhammadiyah 3 Makassar which is proven to show that the data is normally distributed and homogeneous. The results of hypothesis testing show a significance value of 0.007 <0.005 with an average posttest score of 70.60 for the experimental class and 64.60 for the control class. The t-count value is -3.030 with the same standard deviation in both classes which is 4.427. Based on the results of the study, it can be concluded that the traditional game-based learning method (dende-dende) has an effect on understanding the concept of Indonesian grammar for grade II students of SD Muhammadiyah 3 Makassar. The game (dende-dende) not only preserves cultural values but also effectively improves students' understanding of Indonesian grammar concepts in a more fun and meaningful learning atmosphere.